Looking for Margaret Davenport - Simonsen, Jane (American Studies, 2023)
This account – part history, part reflection –attempts to tell the story of Margaret, the purported wife of George Davenport, lauded as one of the “first white settlers” on the Upper Mississippi. I frame my search for her identity in terms of the “roots narratives” that Jerrod Hayes claims take shape around those “queer” elements that they exclude. I deconstruct the “first white woman” narratives that Margaret haunts but does not inhabit, embarking on what Toni Morrison has described as the hunt “for a drop of blood that means everything and nothing.” In so doing, I implicate myself in assuming that Margaret’s relative absence from the historical record equates with non-whiteness. Entertaining possible permutations of Margaret’s identity—was she white? Indigneous? Black?—I tell the stories of other women who inhabited her home, and whose erasure from family and local histories enables the both the family and the region to retain property in whiteness. Uncovering roots narratives that are marked by indigeneity, indentured servitude, property dispossession and incest, I suggest that searches for history and origins in the Midwest can be just as “rhyzomatic” as transatlantic histories and their outcomes just as queer. If the work of history-telling is to create a balanced account, I insert my own voice as a way to recognize the deficit – the missing figure that, through an absence both racialized and gendered - marks not only my own, but all historical narratives produced by settler cultures.